2021
DOI: 10.1016/j.hlpt.2021.100506
|View full text |Cite|
|
Sign up to set email alerts
|

How Iran responded to expanding need for laboratory services for COVID-19?

Abstract: After the emergence of SARS-CoV-2 in early 2020 in Iran, the rapid response team of Pasteur Institute of Iran was the first lab starting detection and report of suspected human samples. This article is a short summery of all actions from the preparedness for detecting the first cases of COVID-19, expanding the nationwide laboratory service, choosing the suitable laboratory tests and other challenges in laboratory detection during SARS-CoV-2 pandemic in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In February 2020, the rst COVID-19 laboratory was established at the Pasteur Institute of Iran when the commercial kits had not been imported to Iran yet. Thus, this institute was authorized to form the COVID-19 laboratory diagnostic committee and direct the national laboratory diagnostic network with the support of the Ministry of Health (15). Thousands of suspected COVID-19 samples were sent daily to the Pasteur Institute of Iran post the rst case recognition in the country on 18th February 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In February 2020, the rst COVID-19 laboratory was established at the Pasteur Institute of Iran when the commercial kits had not been imported to Iran yet. Thus, this institute was authorized to form the COVID-19 laboratory diagnostic committee and direct the national laboratory diagnostic network with the support of the Ministry of Health (15). Thousands of suspected COVID-19 samples were sent daily to the Pasteur Institute of Iran post the rst case recognition in the country on 18th February 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, Pasture Institute of Iran provided the rst diagnostic laboratory for SARS-CoV-2 infection. All the collected COVID-19 suspected samples were sent to this institute and the educated staff and experts put all their effort day and night to handle the tests immediately and thus prevented from any probable crisis (15,16).…”
Section: Covid-19 By Vaccination and Effective Interventions (6-8)mentioning
confidence: 99%
“…This action was taken in response to the need to create an agile structure for identifying, monitoring and detecting emerging infectious diseases (Table 1). 5 From its establishment until the COVID-19 pandemic, the team…”
Section: Establishment Of the Covid-19 National Laboratory Network In...mentioning
confidence: 99%
“…Shortly after the news of the detection of a novel coronavirus in China on 31 December 2019, the rapid response team decided on January 18, 2020, to use all available capacities to launch diagnostic tests for the emerging virus (named 2019 novel coronavirus [2019‐nCoV] at that time) as soon as possible. In this regard, the following several actions were taken: (1) optimizing the pan‐coronavirus RT‐PCR test that had been designed in 2015 6 ; (2) designing diagnostic tests based on the published protocols of Corman et al 7 and Hong Kong University 8 ; (3) sending a request for clinical kits and positive control to WHO, Pasteur Institute networks, and EVAg; and (4) ordering available commercial kits in the market including PrimerDesign Ltd., UK (COVID‐19 genesig® Real‐Time PCR assay, detecting RdRp gene) 5 . Subsequently, the first COVID‐19 laboratory started working as the national reference laboratory on January 25, 2020, at the IPI, and the readiness to receive suspected samples was formally announced to the Ministry of Health.…”
Section: Establishment Of the Covid‐19 National Laboratory Network In...mentioning
confidence: 99%
“…Interestingly, the multiplex assay showed that the first, second, and third samples (obtained on September 13, 14, and 15, 2021) were positive for HCoV HKU1/ HCoV OC43. To confirm HKU1/ HCoV OC43 infection, a pan coronavirus RT-PCR assay was employed to amplify about 600 bp of the genome [9]. The PCR products were subsequently sequenced with the amplification primers via the Sanger assay by a 3130 Genetic Analyzer (Thermo Fisher Scientific, USA).…”
Section: Case Reportmentioning
confidence: 99%